PENGARUH INSENTIF, KEPEMIMPINAN, IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN KERJA PEGAWAI PADA DINAS PENGELOLAAN KEUANGAN DAERAH PROVINSI SUMATERA BARAT - Ana Mersia; Syamsul Amar (Program Studi Magister Manajemen, 2015)
The objective of the study is to examine (1)The effects of leadership on organizational climate. (2)The effect of incentives, leadership, and organizational climate on job satisfaction and (3)The effect of incentives, leadership, organizational climate and job satisfaction on work commitments. The scope of research was analyze the variables significantly influence incentives, leadership, organizational climate, and job satisfaction on job satisfaction variables through intermediate variable (job satisfaction). The research population was all employees of the Office of Financial Management of West Sumatera Province, amounting to 279 people. Sampling was done by stratified random sampling proportional amount to 162 people. Data were collected by questionnaire Likert scale models that have tested the validity and reliability. Techniques of data analysis is path analysis. Hypothesis testing used the test f. The results showed that: (1)leadership has a significant effect on organizational climate. (2) incentives, leadership, and organizational climate have significant effect on job satisfaction. (3) incentives, leadership, organizational climate, and job satisfaction have significant effect on work commitments. It known that the direct effect of leadership on job commitment and job satisfaction directly influences the work commitments and the effect of incentives on work commitment. While the indirect effect of organizational climate on work commitment through job satisfaction larger than the indirect effect of leadership on work commitment through job satisfaction and indirect effects of leadership on work commitment through organizational climate and influence of indirect incentives to work commitment through job satisfaction. Keywords: incentives, leadership, organizational climate, job satisfaction, work commitments